Cometabolism of 17α-ethynylestradiol by nitrifying bacteria depends on reducing power availability and leads to elevated nitric oxide formation - Qi Sheng; Ming Yi; Yujie Men; Huijie Lu (Environment International, 2021)
17α-ethynylestradiol (EE2) is a priority emerging contaminant (EC) in diverse environments that can be cometabolized by ammonia oxidizing bacteria (AOB). However, its transformation kinetics and the underlying molecular mechanism are unclear. In this study, kinetic parameters, including maximum specific EE2 transformation rate, EE2 half-saturation coefficient, and EE2 transformation capacity of AOB were obtained by using the model AOB strain, Nitrosomonas europaea 19718. The relationship between EE2 cometabolism and ammonia oxidation was divided into three phases according to reducing power availability, namely “activation”, “coupling”, and “saturation”. Specifically, there was a universal lag of EE2 transformation after ammonia oxidation was initiated, suggesting that sufficient reducing power (approximately 0.95 ± 0.06 mol NADH/L) was required to activate EE2 cometabolism. Interestingly, nitric oxide emission increased by 12 ± 2% during EE2 cometabolism, along with significantly upregulated nirK cluster genes. The findings are of importance to understanding the cometabolic behavior and mechanism of EE2 in natural and engineered environments. Maintaining relatively high and stable reducing power supply from ammonia oxidation can potentially improve the cometabolic removal of EE2 and other ECs during wastewater nitrification processes.